Efetividade da abordagem de orientação cognitiva para o desempenho ocupacional diário (co-op) na melhoria do desempenho funcional de crianças e adolescentes com paralisia cerebral - Larissa Keli de Sousa (2017)
Among the various types of intervention procedures used with children with cerebral palsy (CP), top-down approaches have been showing better evidences of improving performance on motor and self-care activities. Among top-down approaches, the Cognitive Orientation to Daily Occupational Performance (CO-OP), although developed for children with Developmental Coordination Disorder, seems to be a viable option for children with CP. The aims of this paper were: to investigate whether children and adolescents with CP submitted to CO-OP in a clinical setting would show higher gains in functional performance than when submitted to Current Treatment of Occupational Therapy (C-OT), whether children and adolescents with CP retain acquired skills, whether they would transfer and generalize strategies and learned skills, and whether there would be improvements in manual dexterity and gross motor function (secondary outcomes). A crossover randomized clinical trial was conducted with 12 children and adolescents aged six to 15 years old. All participants were evaluated with the Kaufman Brief Intelligence Test 2ª edition (KBIT-2) to estimate intelligence coefficient. The Canadian Occupational Performance Measure (COPM), the Perceived Efficacy and Goal Setting System (PEGS) and the Performance Quality Rating Scale Generic (PQRS-G) were used to identify goals and measure changes (primary outcomes). The participants were randomized into CO-OP1 and CO-OP2 groups. The interventions CO-OP and C-OT lasted 13 sessions and the assessments were conducted before and after CO-OP intervention, as well as at three and six months after CO-OP intervention. Clinical parameters and Generalized Equations Estimating (GEE) were used to evaluate CO-OP effects over time, with significance level established at p=0,05. There were statistical and clinical significant improvements on COPM performance and satisfaction as scored by the participants of the CO-OP1 (p=0,000) and CO-OP2 (p=0,001), as well as in parents perception of CO-OP1 (p=0,000). There was also statistically significant change in the PQRS-G for both groups (p=0,000 and p=0,044) after CO-OP, but not after C-OT. Evidence of skill transfer was observed in two participants from each group according to the children and adolescents perception. The acquired skills were retained, because after CO-OP there were no further significant changes on functional skill scores. Improvements on manual dexterity were observed in both groups three and six months after CO-OP and statistical significant improvements in GMFM-88 gross motor function only for the CO-OP2 group. The CO-OP approach was effective when used in a Brazilian rehabilitation context, promoting benefits on the functional performance of children and adolescents with CP.